The Spread of Antibiotic-Resistant Bacteria in Water Sources and Soil Sediments in Urban Communities and the Health Risks to People in the Community - Threedeach, Simanata; Moungsree, Savitree; Thummakul, Doungnetre; Netchu, Kanokaon; Suwanprapa, Montol (Princess of Naradhiwas University Journal, 2025)
Background and Objectives This research aimed to study the spread of antibiotic-resistant bacteria in the environment and the health risks from environmental pollution in water sources as perceived by community members. Methods This study involved analyzing environmental samples from canal water and soil sediment in urban community areas, where urban lifestyles are a significant source of antibiotic-resistant bacteria. The study compared community A, a densely populated residential area surrounded by high-rise buildings, with community B, which has a sparser residential area and practices agriculture. The study monitored the gastrointestinal pathogens Escherichia coli, Staphylococcus sp., and Enterococcus sp. and tested for resistance to the antibiotics Tetracycline (TC), Ciprofloxacin (CIP), and Trimethoprim/sulfamethoxazole (SXT) at the minimum inhibitory concentration (MIC) that creates antibiotic-resistant bacteria. Results The research results showed the presence of Staphylococcus sp. (3.1x10^4 - 5.3x10^4 CFU/g wet weight) and Enterococcus sp. (3.4x10^4 - 1.7x10^5 CFU/g wet weight) accumulated in high amounts in the canal bank sediment compared to E. coli (1.0x103-4.9x103 CFU/g wet weight), while community water sample A had higher levels of all 3 bacterial groups compared to community B, with values of 4.9x101-8.2x102 CFU/mL and 1.7x101-1.1x102 CFU/mL, respectively. Additionally, three antibiotic-resistant bacteria were found at higher levels too. E. coli in community water sample A that survived were resistant to TC, CIP, and SXT at an average of 28.2-49.1%, and Staphylococcus sp. from the water samples from both communities had an average resistance to SXT of 35.0-65.5, indicating that activities in densely populated residential areas negatively impact the spread of antibiotic-resistant bacteria. Regarding health risks from environmental pollution in water sources as perceived by community members, an accidental sample of 80 people was selected, with 65% being elderly. The survey was conducted in community A using a quality-checked questionnaire. The research findings showed that health risks with low severity included disease contagions, unpleasant odors, and skin rashes, with percentages of 3.75%, 3.75%, and 1.25%, respectively. Health risks with very low severity included disease contagions, unpleasant odors, skin rashes, and difficulty breathing, with percentages of 81.25%, 53.75%, 41.25%, and 36.25%, respectively. Conclusion and Recommendations It is essential to develop effective water source monitoring and management measures to reduce health risks to community members.